Exploring the diversity of Diplostomum (Digenea: Diplostomidae) in fishes from the River Danube using mitochondrial DNA barcodes - Kudlai, Olena; Oros, Mikuláš; Kostadinova, Aneta; Georgieva, Simona (Parasites & vectors, 2017)
BACKGROUND: Metacercariae of Diplostomum are important fish pathogens, but reliable data on their diversity in natural fish populations are virtually lacking. This study was conducted to explore the species diversity and host-parasite association patterns of Diplostomum spp. in a large riverine system in Europe, using molecular and morphological data. METHODS: Twenty-eight species of fish of nine families were sampled in the River Danube at Nyergesújfalu in Hungary in 2012 and Štúrovo in Slovakia in 2015. Isolates of Diplostomum spp. were characterised morphologically and molecularly. Partial sequences of the 'barcode' region of the cytochrome c oxidase subunit 1 (cox1) and complete sequences of the nicotinamide adenine dinucleotide dehydrogenase subunit 3 (nad3) mitochondrial genes were amplified for 76 and 30 isolates, respectively. The partial cox1 sequences were used for molecular identification of the isolates and an assessment of haplotype diversity and possible host-associated structuring of the most prevalent parasite species. New primers were designed for amplification of the mitochondrial nad3 gene. RESULTS: Only lens-infecting Diplostomum spp. were recovered in 16 fish species of five families. Barcoding of representative isolates provided molecular identification for three species/species-level genetic lineages, D. spathaceum, D. pseudospathaceum and 'D. mergi Lineage 2', and three single isolates potentially representing distinct species. Molecular data helped to elucidate partially the life-cycle of 'D. mergi Lineage 2'. Many of the haplotypes of D. spathaceum (16 in total), D. pseudospathaceum (15 in total) and 'D. mergi Lineage 2' (7 in total) were shared by a number of fish hosts and there was no indication of genetic structuring associated with the second intermediate host. The most frequent Diplostomum spp. exhibited a low host-specificity, predominantly infecting a wide range of cyprinid fishes, but also species of distant fish families such as the Acipenseridae, Lotidae, Percidae and Siluridae. The nad3 gene exhibited distinctly higher levels of interspecific divergence in comparison with the cox1 gene. CONCLUSIONS: This first exploration of the species diversity and host ranges of Diplostomum spp., in natural fish populations in the River Danube, provided novel molecular, morphological and host-use data which will advance further ecological studies on the distribution and host ranges of these important fish parasites in Europe. Our results also indicate that the nad3 gene is a good candidate marker for multi-gene approaches to systematic estimates within the genus.
Keywords: Diplostomidae; Phylogeny; Hungary; Metacercariae; Trematoda; Fish Diseases; mitochondriální DNA; DNA, Mitochondrial; Europe; zvířata; genetická variace; Slovakia; oční čočka; River Danube; ryby; Fishes; Slovenská republika; řeky; Freshwater fishes; Barcodes; Diplostomum; Rivers; DNA Barcoding, Taxonomic; nemoci ryb; Maďarsko; Eye Diseases; Genetic Variation; Animals; Lens, Crystalline; nad3; cox1; fylogeneze; taxonomické DNA čárové kódování; oční nemoci